Sun Inspired Tri-Band FSS based Absorber with High Angular Stability and Polarization Insensitivity Used for RF Energy Harvesting Applications - Bhattacharya S.; Bhattacharya S.; Thottappan M. (My University, 2025)
A compact and low profile FSS based absorber incorporating sun inspired geometry enclosed within a slotted rectangular ring is reported in this paper. The proposed triple layered(patch-substrate-ground) geometry yielded a closely spaced tri- band response centered at resonants 3.1 GHz, 4.2GHz and 6.1GHz with near unity absorptivities. The proposed meta cell exhibits four-fold symmetry leading to the structure being insensitive to change in polarization. The meta atom designed using the impedance matching theorem shows stable characteristics over a wide range of oblique incidence angle. The geometrical structure is designed in such a way so that it can be employed as a device for RF energy harvesting applications for the 5G and 6G technology which falls in the Sub Gigahertz. © 2024 IEEE.